State of the world 2014: governing for sustainability (Washington, DC, 2014)
"Citizens expect their governments to lead on sustainability. But from largely disappointing international conferences like Rio II to the U.S.’s failure to pass meaningful climate legislation, governments’ progress has been lackluster. That’s not to say leadership is absent; it just often comes from the bottom up rather than the top down. Action—on climate, species loss, inequity, and other sustainability crises—is being driven by local, people’s, women’s, and grassroots movements around the world, often in opposition to the agendas pursued by governments and big corporations.